Advances in magnetic resonance. - Waugh, John S. (Academic Press, 1966)
Advances in Magnetic Resonance, Volume 2, features a mixture of experimental and theoretical contributions. The book contains four chapters and begins with an ambitious and general treatment of the problem of signal-to-noise ratio in magnetic resonance. This is followed by separate chapters on the interpretation of nuclear relaxation in fluids, with special reference to hydrogen; and various aspects of molecular theory of importance in NMR.